Applying limestone or basalt in combination with bio-fertilizer to sustain rice production on an acid sulfate soil in Malaysia - Panhwar, Qurban Ali; Naher, Umme Aminun; Jusop, Shamshuddin; Othman, Radziah; Ismail, Mohd Razi (MDPI, 2016)
A study was conducted to determine the efficacy of applying ground magnesium limestone (GML) or ground basalt in combination with bio-fertilizer to sustain rice production on an acid sulfate soil in Malaysia. Soils from Kelantan Plains, Malaysia, were treated with GML, ground basalt, bio-fertilizer, GML + bio-fertilizer, and ground basalt + bio-fertilizer (4 t·ha−1 each). Results showed that soil fertility was improved by applying the soil amendments. GML and basalt contain some Zn and Cu; thus, application of these amendments would increase their contents in the soil needed for the healthy growth of rice. Basalt applied in combination with bio-fertilizer appeared to be the best agronomic option to improve the fertility of acid sulfate soils for sustainable rice production in the long run. In addition to increasing Ca, Mg, Zn, and Cu reserves in the soil, water pH increased and precipitated Al3+ and/or Fe2+. Ground basalt is cheaper than GML, but basalt dissolution in the acidic soil was slow. As such, its ameliorative effects could only be seen significantly from the second season onwards. The specially-formulated bio-fertilizer for alleviating the infertility of acid sulfate soil could also enhance rice growth. The use of the bio-fertilizer fortified with N2-fixing bacteria is a green technology that would help reduce NO3− and/or NO2− pollution and reduce the cost of rice production. The phosphate-solubilizing bacteria (PSB) present in the bio-fertilizer not only increased the available P, but also helped release organic acids that would inactivate Al3+ and/or Fe2+ via the process of chelation.